2012
DOI: 10.1007/s10924-012-0422-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Differences Between Lignin Model Polymers Synthesized from Various Monomers

Abstract: In a plant cell wall, lignin is synthesized from several monomeric precursors, combined in various ratios. The variation in monomer type and quantity enables multifunctional role of lignin in plants. Thus, it is important to know how different combinations of lignin monomers impact variability of bond types and local structural changes in the polymer. Lignin model polymers are a good model system for studies of relation between variations of the starting monomers and structural variations within the polymer. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Their fluorescence spectra (Fig. 3 ) indicates maximum λ EX /λ EM of 372 nm/439 nm and 382 nm/450 nm, respectively, in agreement with the values previously presented 36 . Patterns of native lignocellulosic samples (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Their fluorescence spectra (Fig. 3 ) indicates maximum λ EX /λ EM of 372 nm/439 nm and 382 nm/450 nm, respectively, in agreement with the values previously presented 36 . Patterns of native lignocellulosic samples (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In-depth characterization of model CA dilignols suggested that fluorophores are not significantly electronically coupled to one another and can be seen as isolated fluorophores 27 . But even model lignin polymers fluorescence differs significantly depending on their composition 36 . Recently, it has been proposed that lignin fluorescence may originate from its aggregation due in particular to clustering of the carbonyl groups 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Compression wood lignin has greater p ‐hydroxyphenyl unit content localised to the outer secondary wall (Terashima & Fukushima, ). There are indications that in lignin, polymers containing a higher amount of p ‐hydroxyphenyl units, chain structures consisting of alternating C = C/C‐C bonds are formed (Donaldson et al ., ; Djikanovic et al ., ). Such structures may be responsible for shorter lifetimes, higher fluorescence intensity and red shift of the long‐wavelength emission maxima in compression wood compared to normal wood.…”
Section: Discussionmentioning
confidence: 97%
“…It has the advantage of requiring little tissue preparation, and there are imaging devices adapted to observe samples on a macroscopic scale [2,34]. In plant cell walls, lignin and hydroxycinnamic acids account for most of the autofluorescence and can be differentiated by their autofluorescence profiles [33][34][35][36][37][38][39][40][41]. Hydroxycinnamic acids emit blue fluorescence under UV excitation at approximately 350 nm [37,38], while lignin excited using UV and visible light emits blue, green and red fluorescence [35,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In plant cell walls, lignin and hydroxycinnamic acids account for most of the autofluorescence and can be differentiated by their autofluorescence profiles [33][34][35][36][37][38][39][40][41]. Hydroxycinnamic acids emit blue fluorescence under UV excitation at approximately 350 nm [37,38], while lignin excited using UV and visible light emits blue, green and red fluorescence [35,[39][40][41]. The relative proportions of phenolic compounds and their environment (pH, presence of quenching molecules, etc.)…”
Section: Introductionmentioning
confidence: 99%